RANCANG BANGUN PEMBANGKIT LISTRIK TENAGA MIKRO HIDRO (PLTMH) WADUK PDAM BENGKALIS - Zainal, Zainal Abidin; Faizal, Wan M; Budiyanto, Nirwan (Politeknik Negeri Bengkalis, 2023)
This research uses a descriptive analysis method with a qualitative approach. The aim of this research is to obtain feasibility recommendation for the Municipal Waterworks (PDAM) of Bengkalis’ drainage to be functioned as a forebay. The feasibility recommendation will be obtained through comparing the observation results of measurement on the width, length, and height of standing water on the drainage of the reservoir to the calculation results. The result of this research shows that the width of drainage based on observation is 1,85m, with the calculation of 1,72m, gap of 0,13m, and length of drainage based on observation is 6,85m, calculation of 6,63m, gap of 0,22m length of head based on observation of 0,58m, calculation of 0,68m, gap of -0,10m with turbine output of 1,74Kw, power output of 1,53Kw and generator power capacity of 1,69Kw, and with simulating the height of standing water of 0,53m dan 0,48m, results turbine output of 1,59Kw dan 1,44Kw, power output of 1,40Kw and 1,27Kw and the generator power capacity of 1,54Kw dan 1,40Kw. It can be concluded that the drainage of Bengkalis PDAM’s reservoir can be functioned and feasible to be implemented as a forebay of Micro Hydro Power Plant (PLTMH). Keywords : PLTMH, Forebay, Drainage, Reservoir, Power